2015
DOI: 10.1371/journal.pgen.1005148
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Inheritance of Diet-Induced Genome Rearrangements in Drosophila

Abstract: Ribosomal RNA gene (rDNA) copy number variation modulates heterochromatin formation and influences the expression of a large fraction of the Drosophila ge-nome. This discovery, along with the link between rDNA, aging, and disease, high-lights the importance of understanding how natural rDNA copy number variation arises. Pursuing the relationship between rDNA expression and stability, we have discovered that increased dietary yeast concentration, emulating periods of dietary excess during life, results in somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 91 publications
3
74
3
Order By: Relevance
“…Work in Drosophila has demonstrated a paternal contribution to metabolic programming (Valtonen et al , 2012b; Ost et al , 2014; Aldrich and Maggert, 2015). Exposure of male flies to a low-protein diet from embryo through adulthood resulted in progeny with shortened developmental times and larger male offspring, but no change in female offspring size, relative to paternal males raised on standard food (Valtonen et al , 2012b).…”
Section: Metabolic Programming In the Offspringmentioning
confidence: 99%
See 3 more Smart Citations
“…Work in Drosophila has demonstrated a paternal contribution to metabolic programming (Valtonen et al , 2012b; Ost et al , 2014; Aldrich and Maggert, 2015). Exposure of male flies to a low-protein diet from embryo through adulthood resulted in progeny with shortened developmental times and larger male offspring, but no change in female offspring size, relative to paternal males raised on standard food (Valtonen et al , 2012b).…”
Section: Metabolic Programming In the Offspringmentioning
confidence: 99%
“…Taking full advantage of the benefits of fly genetics and dietary manipulation, two groups have uncovered profound insight into the mechanistic underpinnings of metabolic programming, highlighting a key role for genomic alteration (Ost et al , 2014; Aldrich and Maggert, 2015). Male flies fed a protein-rich diet exhibit decreased rDNA copy numbers resulting in rDNA instability in both somatic and germ cells which was InR-dependent (Aldrich and Maggert, 2015).…”
Section: Metabolic Programming In the Offspringmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, even in rapidly growing yeast cells, about 50% of the rDNA copies are silenced through epigenetic modification (Lempiäinen & Shore 2009). Intriguingly, a recent study in Drosophila found that increasing levels of dietary yeast during development lead to increased expression of ribosomal RNA genes during development and that this in turn is correlated with increased rDNA instability and loss of rDNA copies in adults (Aldrich & Maggert 2015). Furthermore, the loss of rDNA copies is known to be associated with the loss of heterochromatic induced silencing (Paredes & Maggert 2009) and the loss of heterochromatin in turn, is known to de-repress RNA synthesis and decrease lifespan in Drosophila (Larson et al 2012).…”
Section: Larval Dietmentioning
confidence: 99%